Laparoscopic removal of an ingested fish bone that penetrated the stomach and was embedded in the pancreas: a case report - Kosuke Mima; Hidetaka Sugihara; Rikako Kato; Chihiro Matsumoto; Daichi Nomoto; Hironobu Shigaki; Junji Kurashige; Mitsuhiro Inoue; Shiro Iwagami; Takao Mizumoto; Tatsuo Kubota; Nobutomo Miyanari (Surgical Case Reports, 2018)
Abstract Background The gastrointestinal tract can occasionally be perforated or penetrated by an ingested foreign body, such as a fish bone. However, there are very few reported cases in which an ingested fish bone penetrated the gastrointestinal tract and was embedded in the pancreas. Case presentation An 80-year-old male presented with epigastric pain. Computed tomography of the abdomen showed a linear, hyperdense, foreign body that penetrated through the posterior wall of the gastric antrum. There was no evidence of free air, abscess formation, migration of the foreign body into the pancreas, or pancreatitis. As the patient had a history of fish bone ingestion, we made a diagnosis of localized peritonitis caused by fish bone penetration of the posterior wall of the gastric antrum. We first attempted to remove the foreign body endoscopically, but failed because it was not detected. Hence, an emergency laparoscopic surgery was performed. A linear, hard, foreign body penetrated through the posterior wall of the gastric antrum and was embedded in the pancreas. The foreign body was safely removed laparoscopically and was identified as a 2.5-cm-long fish bone. Intraperitoneal lavage was performed, and a drain was placed in the lesser sac. The patient recovered without complications and was discharged on the 7th postoperative day. Conclusion Laparoscopic surgery could be performed safely for the removal of an ingested fish bone embedded in the pancreas.